Individual to collective adaptation through incremental change in Colorado groundwater governance - Loos, Jonathon R.; Andersson, Krister; Bulger, Shauna; Cody, Kelsey C.; Cox, Michael; Gebben, Alexander; Smith, Steven M. (Frontiers in Environmental Science, 2022)
Designing adaptive institutions for achieving sustainable groundwater use is a central challenge to local and state governments. This challenge is exacerbated by the growing impacts and uncertainty of climate change on water resources. Calls to reform water governance systems are often made in the context of these challenges, and reform efforts increasingly emphasize the need for solutions that are locally designed and administered. Such reforms often require fundamental institutional change that is difficult to achieve amid the myriad forces that stabilize and reproduce existing institutional structures and functions. In practice, governance change is instead overwhelmingly incremental and tends to be punctuated by periods of adjustment in response to social or environmental shocks and disturbances. We present a comparative study of four major Colorado river basins and examine how each has evolved distinct arrangements of groundwater governance in response to regulatory and drought disturbances over the past century. We interrogate concepts of path-dependence and apply a historical lens to understand why locally designed institutions for self-regulation emerge in some Colorado groundwater basins but not in others. We uncover a pattern of collective action by groundwater users that first seeks to oppose state regulation, followed by acceptance and efforts to comply, and eventual attempts to get ahead of state regulation by enacting local institutions for self-regulation. We report these findings and discuss the insights they offer for understanding how adaptive natural resources institutions are shaped through time by the constraints and opportunities of path-dependence and local contexts.